Impact Engineering of Composite Structures - Abrate, Serge; SpringerLink (Online service) (Vienna : Springer Vienna, 2011)
The book provides an introduction to the mechanics of composite materials, written for graduate students and practitioners in industry. It examines ways to model the impact event, to determine the size and severity of the damage and discusses general trends observed during experiments.
Keywords: Engineering; Vibration; Astronautics; Engineering; Vibration, Dynamical Systems, Control; Automotive Engineering; Aerospace Technology and Astronautics